Is Vestibular Meniere's Disease Associated With Endolymphatic Hydrops? - Morita, Yuka; Takahashi, Kuniyuki; Ohshima, Shinsuke; Yagi, Chihiro; Kitazawa, Meiko; Yamagishi, Tatsuya; Izumi, Shuji; Horii, Arata (Frontiers in Surgery, 2020)
Background: Vestibular Meniere's disease (American Academy of Ophthalmology and Otolaryngology, 1972) also known as possible Meniere's disease (American Academy of Otolaryngology Head and Neck Surgery, 1995) or vestibular type of atypical Meniere's disease (V-AMD) (Japan Society for Equilibrium Research, 2017) is characterized by an episodic vertigo without hearing loss. Though named as Meniere's disease (MD), this entity may not be caused solely by endolymphatic hydrops (EH). Objective: To estimate the role of EH in vestibular Meniere's disease in comparison with definite Meniere's disease. Methods: Thirty patients with unilateral definite MD and 16 patients with vestibular Meniere's disease were included. Those who met the criteria for definite or probable vestibular migraine were excluded. All patients underwent vestibular assessments including inner ear MRI 4 h after intravenous gadolinium injection, bithermal caloric testing, directional preponderance of vestibulo-ocular reflex in rotatory chair test, cervical- and ocular-vestibular evoked myogenic potential, stepping test, dizziness handicap inventory (DHI), and hospital anxiety and depression scale (HADS). All above tests and frequency/duration of vertigo spells were compared between vestibular Meniere's disease and MD. Results: Even in unilateral MD, cochlear and vestibular endolymphatic hydrops (c-, v-EH) were demonstrated not only in the affected side but also in the healthy side in more than half of patients. Positive rate of v-EH in vestibular Meniere's disease (68.8%) was as high as that of MD (80%). In vestibular Meniere's disease, the number of bilateral EH was higher in the vestibule (56.3%) than that in the cochlea (25.0%). There were no differences in vestibular tests and DHI between vestibular Meniere's disease and MD; however, the frequency of vertigo spells was lower in vestibular Meniere's disease (p = 0.001). The total HADS score in the MD group was significantly higher than that in the vestibular Meniere's disease group. Conclusions: MD is a systemic disease with bilateral involvement of inner ears. V-EH is a major pathophysiology of vestibular Meniere's disease, which would precede c-EH in the development of vestibular Meniere's disease, a milder subtype of MD. MRI is useful for differentiating MD from other vertigo attacks caused by different pathologies in bringing EH into evidence.